FENOMENA GEOLOGI DALAM AL-QUR’AN: Pembentukan Gunung, Gempa Bumi, dan Pergerakan Lempeng Tektonik - Haila Fardyatullail; Nurul Marfu’ah; Rahimia Nuzula Salma; Hilma Radhia Mahmudah (Jurnal Al I'jaz, 2025)
This study aims to explore the correlation between the concept of geophysics or the movement of the earth and the verses of the Qur’an that describe various natural phenomena in the universe. These include the movement of the earth, its rotation, and the geological changes it creates. This movement includes tectonic plate movements, which can cause earthquakes, volcanic activity, mountain formation, and all other geological processes that affect the earth's structure. In addition, the Qur’an, as a guide for human life, mentions various aspects related to the movement of the earth, including cosmological issues and natural phenomena that can be connected with modern scientific knowledge. In this research, the researcher attempts to interpret several verses in the Qur’an that relate to the movement of the earth, such as the rotation of the sun and the earth, and to instill a holistic understanding of the universe that connects religious teachings with scientific knowledge. Through a scientific interpretive approach to the verses of the Qur’an, this study aims to provide new insights into the correlation between the religious teachings in the Qur’an and modern scientific knowledge in explaining the phenomena on earth.